The Role of Assessment in Self-Control of Learning - Martinez, Maria Stella (Íkala, Revista de Lenguaje y Cultura, 1996)
This paper discusses the role of assessment as an effective variable which influences the process of building and managing students' own learning as found in a classroom experiment carried out in ESP courses at Universidad del Norte, Barranquilla, Colombia. The overall analysis drawn upon teachers' and students' perceptions of the whole process revealed that getting students motivated in a self-control process of their own learning cannot be achieved simply by developing awareness-raising activities, but that these ought to be integrated with new assessment procedures. In doing so, a shift from traditional paradigms based on product-oriented procedures to more process oriented practices is required.